NGHIÊN CỨU TỔNG HỢP DÂY NANO POLYPYROL BẰNG PHƯƠNG PHÁP ĐIỆN HÓA, ỨNG DỤNG CHO CẢM BIẾN HÓA HỌC - Tuấn, Chu Văn; Trung, Trần; Tuấn, Mai Anh (Vietnam Journal of Chemistry, 2012)
This paper presents the results of polypyrrole nanowires prepared by electrochemical method (Cyclic Voltammograms–CV). The surface morphology structure of polypyrrole nanowires were measured and analyzed by scanning electronic microscope (FE-SEM). Chemical elements and binding in polymer layer will be analyzed by ultraviolet spectrum (UV-Vis) and infrared spectrum (FT-IR). Polypyrrole nanowires with a diameter of 5 nm to 50 nm, surface of polypyrrole membrane has the high level of uniformity and porosity very suitable for application in chemical sensors. Keywords: Polypyrrole, nanowires, Cyclic voltametry.